TECHNOLOGY TO IMPROVE CHILD PROTECTION MECHANISMS IN GENERAL SECONDARY SCHOOLS - A.K.Kadirekova (Scholar Express Journal, 2021)
The article deals with the model of ensuring the rights of children, improving the mechanism of protection of children's rights, "child", "children's rights". The effectiveness of children’s knowledge has been revealed in child rights in general secondary schools.
Keywords: Children; Child Rights; Protection Mechanisms; Model